Potential of Solanum betaceum to improve cognition: A systematic review of animal studies - Hana Aqilah Nur Imania; Aida Fahira Rachma; Lady Aqnes Kurniawati; Hanik Badriyah Hidayati; Citrawati Dyah Kencono Wungu; Muhammad Nazmuddin (GarVal Editorial Ltda., 2024)
Context: Solanum betaceum is rich in bioactive compounds associated with various health applications, including plausible benefits on cognitive impairment caused by neurodegenerative diseases such as Alzheimer's disease (AD). Aims: To investigate the potential benefit of consuming S. betaceum to alleviate cognitive and memory decline. Methods: The review was conducted as a systematic review of an in vivo animal study. A search was performed of five databases using the keywords: "solanum betaceum", "S. betaceum", "tamarillo", "neurodegenerative diseases", "memory loss", "cognitive impairment". SYRCLE tool was used to assess the risk of bias. Data on the underlying molecular mechanisms of behavioral efficacy was additionally collected. Results: A total of 66 journals were retrieved from the databases, resulting in 3 eligible studies. All included studies used albino rats as an AD animal model that were accustomed to laboratory conditions for about a week prior to the disease induction. In two studies, aluminum chloride (AlCl3) was utilized to induce memory deficit, while another study used cigarette smoke. The result indicated that S. betaceum contained compounds such as phenolic and anthocyanin, which were plausibly responsible for the positive cognitive outcomes through molecular interaction with intracellular signaling protein cascades associated with anti-inflammation, brain oxygenation, synaptic plasticity, and cell viability. Further preclinical studies are needed to confirm these potentials. Conclusions: This systematic review of the current evidence on the behavioral and biological influences of S. betaceum administration on AD animal models pointed out that the fruit might improve cognitive performance and prevent cognitive deterioration raised by several neurotoxins.